2005
DOI: 10.1038/nature03380
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide non-mendelian inheritance of extra-genomic information in Arabidopsis

Abstract: A fundamental tenet of classical mendelian genetics is that allelic information is stably inherited from one generation to the next, resulting in predictable segregation patterns of differing alleles. Although several exceptions to this principle are known, all represent specialized cases that are mechanistically restricted to either a limited set of specific genes (for example mating type conversion in yeast) or specific types of alleles (for example alleles containing transposons or repeated sequences). Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
160
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 29 publications
11
160
0
5
Order By: Relevance
“…Alternatively, each species of siRNA and heterochromatin transcripts may be differentially mediated by RNA polymerase IV machinery. (107,108) There is no reason to exclude other post-transcriptional regulatory mechanisms such as RNA stability, (109) alternative splicing, RNA processing and editing, and RNA cache (110) that may be involved in the differential accumulation of transcript levels in the allopolyploids. For example, the stability of mRNAs varied from species to species and the half-life of mRNAs produced from progenitors may be directly correlated with differential accumulation of transcripts in the allopolyploids.…”
Section: Transcriptional Regulation In Allopolyploidsmentioning
confidence: 99%
“…Alternatively, each species of siRNA and heterochromatin transcripts may be differentially mediated by RNA polymerase IV machinery. (107,108) There is no reason to exclude other post-transcriptional regulatory mechanisms such as RNA stability, (109) alternative splicing, RNA processing and editing, and RNA cache (110) that may be involved in the differential accumulation of transcript levels in the allopolyploids. For example, the stability of mRNAs varied from species to species and the half-life of mRNAs produced from progenitors may be directly correlated with differential accumulation of transcripts in the allopolyploids.…”
Section: Transcriptional Regulation In Allopolyploidsmentioning
confidence: 99%
“…Recent studies have suggested the involvement of RNA components in rather unexpected cellular functions (Blower et al 2005;Lolle et al 2005;Rassoulzadegan et al 2006). Studies by Pruitt and colleagues (Lolle et al 2005) in Arabidopsis thaliana hypothesized the possibility of RNA as a messenger of non-Mendelian inheritance of extragenomic information.…”
Section: Rnas As Alternate Genome Cachementioning
confidence: 99%
“…13 Perhaps, the most basic question about these mysterious unannotated transcripts, termed TUFs (transcripts of unknown function), is whether or not they encode proteins. The cloning and sequencing of 178 TUFs reveals that most do not possess open-reading frames greater than 100 amino acids.…”
mentioning
confidence: 99%